FEATURES OF X-RAY RADIATION IN SYMBIOTIC STARS - L.A. Pavlova (Academic Scientific Journal of Computer Science, 2019)
Modern observations of X-ray radiation from individual symbiotic stars are given to clarify their nature. Thus, the spectral features in a wide range of X-rays, optical and ultraviolet, and the rapid UV variability found in SU Lyn are consistent with the assumption that this is a symbiotic star with an accreting white dwarf. RT Cru is a prototype of symbiotics without burning shell on a dwarf with a hard type of x-ray radiation, providing an idea of the most internal structures of accretion. The X-ray type of radiation from the symbiotic star V1329 Cyg indicates that some of the high-energy radiation may occur as a result of strikes in the jet and beyond the symbiotic nebula. In the symbiotic recurrent new T CrB, a sharp increase in the rate at which the material reaches the innermost part of the accretion disk, that is, the boundary layer, is found, this can dramatically change its structure. X-ray satellite Suzaku investigated symbiotics in which X-rays exceed 10 keV (T CrB, CH Cyg, V648 Car). Suzaku CD-28 3719, Hen 3-1591, Hen 3-461, EG And and 4 Dra were observed, in which the models are compatible with X-rays emitted in the boundary layer between the accretion disk and the white dwarf. This paper discusses the various observable properties of individual symbiotic stars on space telescopes to identify common features that can explain the nature of symbiotic stars.